IMPLEMENTASI SUPERVISI AKADEMIK KEPALA MIS BATUSANGKAR - Jumadiah, Nur’ani; Nurdia, Oktazil; Rahmi, Rahmi; Rhoni, Rhoni (Graduate Program Magister Manajemen Pendidikan, 2016)
This study aimed at describing the implementation of academic supervision of the principal MIS Batusangkar. This research was qualitative. The subjects of this research were the principal and teachers MIS Batusanggkar. The interview was used on data collection technique.. The results showed that 1) the implementation of the academic supervision was good, it consists of planning, implementation, and evaluation; 2) the techniques used on academic supervision were teachersâ meeting, visiting class, and personal dialogue; and 3) the response of teachers to the implementation of the supervision were very positive.Â Keywords: Academic Supervision, Principal, Primary School, BatusangkarÂ